E-WOM, VIRAL MARKETING, AND MUSLIM FASHION PURCHASE DECISIONS - Ardella Ninda Safitri; Muhammad Zakiy; Sutrisno Sutrisno (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2026)
The increasingly widespread use of digital media has changed consumer behavior patterns in purchasing Muslim fashion products today. This is reflected in the role of electronic word of mouth (e-WOM) and viral marketing, which are now important strategies for companies in influencing the purchasing decisions of Generation Z consumers. Based on this, this study aims to analyze the influence of e-WOM and viral marketing on purchasing decisions of Muslim fashion products among Indonesian Generation Z consumers, with purchase intention as a mediating variable. The study involved 255 Generation Z respondents who were active on digital platforms, using a quantitative method with a Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The results showed that e-WOM and viral marketing had a significant positive effect on purchase intention, while purchase intention also had a significant positive effect on purchase decisions. Furthermore, purchase intention was proven to significantly mediate the influence of e-WOM and viral marketing on purchase decisions. These findings provide important insights for Muslim fashion industry players in designing digital marketing communication strategies that build credibility, emotional engagement, and social validation to encourage purchase intention and its realization among Generation Z consumers. Digital marketing strategies should focus on building trust through positive reviews, collaboration with influencers, and actively monitoring social media interactions to increase consumer loyalty.